Śaivism and the tantric traditions : essays in honour of Alexis G.J.S. Sanderson - Sanderson, Alexis; Goodall, Dominic; Hatley, Shaman; Isaacson, Harunaga, 1965-; Raman, Srilata (Gonda indological studies, 2020)
"Academic study of the tantric traditions has blossomed in recent decades, in no small measure thanks to the magisterial contributions of Alexis G.J.S. Sanderson, until 2015 Spalding Professor of Eastern Religions and Ethics at Oxford University. This collection of essays honours him and touches several fields of Indology that he has helped to shape (or, in the case of the Śaiva religions, revolutionised): the history, ritual, and philosophies of tantric Buddhism, Śaivism and Vaiṣṇavism; religious art and architecture; and Sanskrit belles lettres. Grateful former students, joined by other experts influenced by his scholarship, here offer papers that make significant contributions to our understanding of the cultural, religious, political, and intellectual histories of premodern South and Southeast Asia. Contributors are: Peter Bisschop, Judit Törzsök, Alex Watson, Isabelle Ratié, Christopher Wallis, Péter-Dániel Szántó, Srilata Raman, Csaba Dezső, Gergely Hidas, Nina Mirnig, John Nemec, Bihani Sarkar, Jürgen Hanneder, Diwakar Acharya, James Mallinson, Csaba Kiss, Jason Birch, Elizabeth Mills, Ryugen Tanemura, Anthony Tribe, and Parul Dave-Mukherji"--